THE RELEVANCE OF THE BOUNDARY BETWEEN LEADERSHIP AND MANAGEMENT IN THE MODERN ERA - Julianto, Pebi (Economic and Bussiness Faculty, Dr Soetomo University, 2025)
This research aims to revisit the relevance of the boundary between leadership and management in the dynamic and uncertain context of modern organizations. Using a qualitative approach based on literature review, this study explores an in-depth understanding of the role and interrelationship between the two in contemporary organizational practice. While the classical literature tends to separate leadership and management as two distinct functions, this study shows a paradigm shift towards the integration of both roles in one professional figure. The main update of this study lies in its approach that emphasizes the importance of holistic and strategic human resource development to produce managers who are also capable of being leaders. The study results show that the conceptual separation between leadership and management is increasingly irrelevant, especially in high-performance organizations. Therefore, there is a need for organizational strategies that combine the two as an integrated competency in training, career development, and performance evaluation. The main conclusion confirms that organizational success is determined by the synergy, not the separation, between leadership and management.